A new species and a new record of Liparis sect. Decumbentes (Malaxidinae, Orchidaceae) from Peru - Alexander Damián; Gerardo A. Salazar; Leyda Rimarachín (PhytoKeys, 2020)
A new species of Liparis sect. Decumbentes, Liparis sessilis Damián, Salazar & Rimarachín, sp. nov is described and illustrated from Amazonas (Perú), including color photographs, a detailed comparison and an identification key to all the species of Liparis sect. Decumbentes. In addition, we report Liparis brachystalix Rchb.f. for the first time for the orchid flora of Peru, and select a lectotype for its synonym, L. commelinoides Schltr.